The interaction of Pax5 (BSAP) with Daxx can result in transcriptional activation in B cells - Emelyanov, Alexander V; Kovac, Cecilia R; Sepulveda, Manuel A; Birshtein, Barbara K (The Journal of biological chemistry, 2002)
Pax5 (BSAP) is essential for B cell development and acts both as a transcriptional activator and a repressor. Using a yeast two-hybrid assay to identify potential coregulators of Pax5, we identified Daxx, a protein that is highly conserved, ubiquitously expressed, and essential for embryonic mouse development. The interaction between Pax5 and Daxx involves the partial homeodomain of Pax5 and the C-terminal fragment of Daxx. A component of promyelocytic leukemia protein nuclear bodies, Daxx has been implicated in apoptosis and characterized as a transcriptional corepressor. Upon transient transfection assay of Daxx in B cells expressing endogenous Daxx and Pax5, we observed not only transcriptional corepression but also, unexpectedly, coactivation in M12.4.1 and A20 mouse B cell lines. Pax5 domains required for coactivation were identified using 293T cells. Coactivation apparently involves recruitment of the CREB binding protein (CBP), because we precipitated complexes containing Pax5, Daxx, and CBP in B cell lines. These data suggest that Daxx can affect Pax5's roles as an activator or repressor in B cells and describe a role for Daxx as a transcriptional coactivator.